Undoing Gender/Dancing Affect - Hölscher, Stefan; Schultz, Laura Luise (Peripeti, 2012)
The article explores the connections between dance, choreography and affect. In a critical negotiation with post-structuralist thinking, especially Judith Butler, Hölscher argues that affect theory from Spinoza through Deleuze and Massumi may constitute a theoretical framework for rethinking the transformative power of the body and its capability for action and agency.